Mandibular trauma severity differences on motorcycle riders using half-face helmet and without helmet based on mandible injury severity score - Syakuran, Muhammad; Hardianto, Andri; Nurwiadh, Agus (Padjadjaran Journal of Dentistry, 2022)
ABSTRACTIntroduction: The popular half-face helmet places the mandible at high risk of fracture during a motorcycle accident. The anatomical shape and position of the mandible make it more frequent to fracture. The purpose of this study was to compare the severity of mandibular trauma in motorcyclists using half face helmets and without using a helmet based on the Mandible Injury Severity Score (MISS). Methods: This research was a prospective cross-sectional study on 60 research subjects at the Emergency Unit of Hasan Sadikin Hospital, Bandung, between July 2019 - February 2020. The data were analyzed with the Mann-Whitney test to see the severity of mandibular trauma using a half face helmet and without a helmet based on MISS (Mandible Injury Severity Score). Results: Of 60 subjects of motorcycle accidents, 58.3% were <25 years old, 38 (63.3%) used half face helmets and 22 (36.7%) non-helmets, 83.3% of the patients were drivers, and 11.7% were passengers. Most fracture sites are parasymphysis, corpus, condylus, symphysis, and subcondylar. 48.3% of subjects had malocclusion, 56.5 with mild displacement, and 43,3% with moderate removal. The average MISS score for half face helmet users was 5.71 and compared to 7.45 for non-helmets. Based on the Mann Whitney test results, the MISS value was not significantly different. Conclusion: Riders who wore half face helmets and those who didn’t wear helmets have the same risk of mandibular trauma based on the MISS. Motorcycle users should use a full face helmet to prevent mandibular fractures during traffic accidents.Keywords: MISS, trauma of mandible, half face helmet, traffic accidents.